(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2019)
Evaluation or Exam is an activity that is inseparable from the activity of teaching and learning carried out by the teacher. Evaluation in the learning process has a very important role because from the evaluation, the teacher will get information about the level of competency of the students, the level of effectiveness of a lesson. For this reason teachers need to be given competencies to develop an adequate evaluation tool so that they can provide the right picture. The focus of this research is 1] How is the effectiveness of tests destraction developed by Diklat participants ? 2] How is the level of difficulty indext of the test ? 3] How is the quality of the descrimination index of the test ? This research method uses a Descriptive approach, with the subjects of the study were 35 English Teachers training participants. While the data collection techniques used the document, the results of the Prediction Tests developed by the training participants and it was analyzed by Anates Version 04. The results of the analysis showed that the effectiveness of destractions were still not good, beside that there were still too difficult and too easy tests.While the Descrimination Index were more than 50 % of the questions withbad different power.